Prey spectra of bornean nepenthes species (Nepenthaceae) in relation to their habitat - H. Adam, Jumaat (Universiti Putra Malaysia Press, 1997)
Examination ofpitcher prey contents of 18 Bomean pitcher plants showed that pitchers attract 17 fauna groups. The upper and lower pitchers trap both flying and creeping fauna but generally the lower pitchers trap more creeping fauna and upper pitchers more flying prey species. Prey composition is generally correlated with habitat; species occupying different habitats in the same locality sometimes show striking differences in prey composition. Formicidae are the most abundant and frequently trapped, and pitchers collected below 100 m altitude contained enormous numbers of ants but their number generally decreased with altitude. However, the number of ants caught per pitcher was variable, e.g. from a few ants to 700 per pitcher in N. rafflesiana. Nepenthes species growing at high altitudes trapped a broader spectrum ofprey than species at lower altitudes. This broad spectrum of prey provides an ample food source for the pitcher-inhabiting predators, particularly Arachnida, which are common in high altitude species.